Movimentos enunciativos na escrita de sujeitos com afasia - Costa, Maria Eduarda Prauchner da (2024)
The field of study encompassing aphasia is extensive. It spans several areas of knowledge, such as Speech Therapy, Psychology, and Neurology, among others, and with linguist Roman Jakobson, aphasia has also come to be studied as a linguistic problem. The author established a typology for aphasia: contiguity disorder and similarity disorder. With the linguist Émile Benveniste, we can study man in language through studies that deal with enunciation, which includes the categories of person, time, and place. According to Benveniste, the speaker appropriates language and immediately places another person as his or her addressee, using specific indices and accessories to express his or her particular relationship with reality. This possibility of studying language in use extends to subjects with aphasia, allowing for analyses of language in disorder. As for the writing of subjects with aphasia, studies are scarce with an enunciative bias, which is a fertile contribution to studies in the linguistic field. Therefore, this research aims to investigate the enunciative movements produced by three subjects with aphasia during the elaboration of written utterances, considering Benveniste’s enunciative theory and Jakobson’s proposition of aphasia. It is a qualitative study; individual and group writing workshops were held with three participants from the Interdisciplinary Coexistence Group (GIC) at the Federal University of Santa Maria to collect the corpus. The results show that the three participants produced written enunciations in which it was possible to observe the enunciative movements but with different predominances and frequencies. From the analyses, it was possible to ascertain that aspects of each subject’s respective aphasia are reflected in their writing, and movements were identified in writing linked to difficulties arising from the similarity disorder but not the contiguity disorder. The occurrence of a new movement, here called testing, was also verified. Finally, we conclude that subjects with aphasia can produce movements in writing influenced by aspects of similarity disorder, which was not observed in the case of contiguity. It is expected that these considerations will help provide a better understanding of the uses and aspects of language in disorder in the enunciative act of writing, thus contributing to linguistic studies in the field of aphasia.